RESEARCH OF THE WAY OF USING CHIA SEEDS IN BAKERY PRODUCTION - Elena Alekseevna Eliseyeva; Anna Viktorovna Borisova (Современная наука и инновации)
Flour confectionery products (FCP), high-calorie foods rich in carbohydrates and defective proteins, poorly assimilated by the human body. The prospect of using plant materials as functional ingredients that reduce energy and enhance the nutritional value of finished products is one of the most urgent areas of food growth. The aim of the study is to study the effect ofchia seeds on the organoleptic and physico-chemical indicators of the quality of flour confectionery products and the choice of the optimal way to use chia seeds in the production of such products.